Cross-linking of starch with reactive extrusion and expansion of extrudates - Seker, M; Sadikoglu, H; Ozdemir, M; Hanna, MA (Marcel Dekker Inc, 2003)
Starch was extruded in a single-screw extruder with sodium hydroxide and three levels of sodium trimetaphosphate (STMP) as 5, 10, and 15% after moisture content was adjusted to 40%. The amount of phosphorus that was incorporated into starch during extrusion, paste viscosity, water solubility index, and sectional expansion index (SEI) of extrudates were determined. A pasting viscosity of phosphorylated starch showed that starch was cross-linked with phosphorus that was incorporated into starch. The cross-linking of starch with STMP and increasing the levels of STMP from 5 to 15% reduced the water solubility index and SEI of extrudates.
Keywords: starch modification; cross-linking; water solubility index; sectional expansion